Analisis Akuntabilitas dan Transparansi terhadap Pengelolaan Blt-Desa 40% pada Masa Pandemi di Desa Sedayulawas - Wahid Suyoto, Agus Wahid Suyoto; Oktafia, Rani (CV. Multi Kreasi Media, 2023)
The purpose of this study is to determine the effect of accountability on the management of BLT-village, determine the effect of transparency on the management of BLT-village, to determine the simultaneous effect of accountability and transparency on the management of BLT-village. This study is a quantitative study using hypothesis testing. Is associative, namely to determine the effect or relationship of two or more variables. The results of this study indicate that there is a positive and significant effect of accountability on BLT-village management, while transparency does not show any effect on BLT-village management. However , simultaneously accountability and transparency have an effect on the management of BLT-Village